Parent Involvement in Homework - Hernández-Prados, María de los Ángeles (2022)
Objective. To know how the family, specifically the parents, affects the pattern of doing homework. Method. A cross-sectional descriptive-evaluative study was conducted using an ad hoc questionnaire. The study included 294 Spanish families whose children were enrolled in the last years of primary school during the 2019-2020 academic year. SPSS 22.0 was used for the statistical analysis. Since the selected variables are nominal, descriptive statistics were used, specifically frequencies and percentages, as well as the use of contingency tables, Pearson’s χ2, Cramer’s V to determine the size of the effect. Results. The main results showed a parental pattern of autonomy in doing homework and the search for support, preferably from relatives instead of external support. This pattern is repeated in sons and daughters, who also do homework at home and invest between 1 and 2 hours, although this depends on the educational course. The place and the person who helps with sons and daughters’ homework assignments are significantly related to the the parents’ educational level. Conclusion. The continuity of the model from fathers and mothers to sons and daughters is significantly demonstrated; this denotes the need for a pedagogical review in this regard, which promotes a different approach to the performance of homework.